Decreta caelestia versus princeps bonus w świetle "Res Gestae" Ammiana Marcellina - Bralewski, Sławomir (Vox Patrum, 2023)
Ammianus Marcellinus in Res Gestae made Emperor Julian the model of a good ruler, even though the gods decided about the defeat of his Persian expedition, in which he himself died. In assessing his character, he assigned him a specific catalogue of virtues. They were headed first by four cardinal virtues: temperantia, prudentia, iustitia and fortitudo, which were additionally supplemented by scientia rei militaris, auctoritas, felicitas and liberalitas. There was no pietas among them, which, according to the Romans, belonged to the fundamental moral virtues, which in the era of the empire became the cardinal virtue of the emperors. This issue has not yet found a proper explanation in the literature on the subject. Analyzing the message of Ammianus Marcellinus, the author of the article showed that he gave up pietas, because the exaggeration with which Julian celebrated traditional cults was widely known. All the more so since this type of abuse generated accusations of superstitio. Undoubtedly, the Ammianus was fascinated by the figure of the emperor, seeing his conduct as a model for other rulers to follow. However, the dependence of felicitas on pietas was a serious problem for him that needed to be resolved. So he decided to abandon the promotion of Julian’s piety as an imperial virtue. However, the historian did not want to explain Julian’s defeat by impiety. So he found an explanation that did not burden the emperor, and it was the capricious nature of Fortune.